Making Things Right: Nurses' Experiences with Workplace Bullying—A Grounded Theory. (8th April 2012) - Gaffney, Donna A.; DeMarco, Rosanna F.; Hofmeyer, Anne; Vessey, Judith A.; Budin, Wendy C.
Abstract : While bullying in the healthcare workplace has been recognized internationally, there is still a culture of silence in many institutions in the United States, perpetuating underreporting and insufficient and unproven interventions. The deliberate, repetitive, and aggressive behaviors of bullying can cause psychological and/or physical harm among professionals, disrupt nursing care, and threaten patient safety and quality outcomes. Much of the literature focuses on categories of bullying behaviors and nurse responses. This qualitative study reports on the experiences of nurses confronting workplace bullying. We collected data from the narratives of 99 nurses who completed an open-ended question embedded in an online survey in 2007. A constructivist grounded theory approach was used to analyze the data and shape a theory of how nurses make things right when confronted with bullying. In a four-step process, nurses place bullying in context, assess the situation, take action, and judge the outcomes of their actions. While many nurses do engage in a number of effective yet untested strategies, two additional concerns remain: inadequate support among nursing colleagues and silence and inaction by nurse administrators. Qualitative inquiry has the potential to guide researchers to a greater understanding of the complexities of bullying in the workplace.